2010
DOI: 10.1021/ic101433t
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Spectro-Structural Correlations of FeIIIZnII Biomimetics for Purple Acid Phosphatases: Relevance to DNA Cleavage and Cytotoxic Activity

Abstract: Purple acid phosphatases (PAPs) are a group of metallohydrolases that contain a dinuclear Fe III M II center (M II = Fe, Mn, Zn) in the active site and are able to catalyze the hydrolysis of a variety of phosphoric acid esters. The dinuclearhas recently been prepared and is found to closely mimic the coordination environment of the Fe III Zn II active site found in red kidney bean PAP (Neves et al. J. Am. Chem. Soc. 2007, 129, 7486). The biomimetic shows significant catalytic activity in hydrolytic reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 54 publications
5
62
0
Order By: Relevance
“…139 A similar effect has been reported in a PAP model with a Fe(III)Zn(II) centre. 141 In neither case, however, were similar correlations found with K m suggesting that the substituent in para-position is primarily affecting nucleophilic activation. The nucleophile in zinc complex-catalysed hydrolysis reactions is in most cases proposed to be a terminal water molecule ( pK a = 6.60-9.5; (A) and (B) in Fig.…”
Section: Dinuclear Zinc Hydrolase Mimicsmentioning
confidence: 92%
See 1 more Smart Citation
“…139 A similar effect has been reported in a PAP model with a Fe(III)Zn(II) centre. 141 In neither case, however, were similar correlations found with K m suggesting that the substituent in para-position is primarily affecting nucleophilic activation. The nucleophile in zinc complex-catalysed hydrolysis reactions is in most cases proposed to be a terminal water molecule ( pK a = 6.60-9.5; (A) and (B) in Fig.…”
Section: Dinuclear Zinc Hydrolase Mimicsmentioning
confidence: 92%
“…Peralta et al reported a linear correlation between the pK a values attributed to deprotonation of the Fe(III)-bound water for complexes with different substituents, methyl, H, Br and NO 2 respectively. 141 These studies suggest that subtle structural changes in the ligand can influence catalytic activity and the acidity of the Cd(II) ions in nucleophilic activation.…”
Section: Dinuclear Cadmium Hydrolase Mimicsmentioning
confidence: 99%
“…The reactions were accompanied by monitoring the increase in the 2,4-dinitrophenolate characteristic absorption band at 400 nm (pH/e L mol À1 cm À1 = 3.5/2125; 4.0/3408; 4.5/7182; 5.0/10 078; 5.5/11 405; 6.0/ 12 004; 6.5-10.0/12 100) at 50°C for the hydrolase-like activity [18] and the formation of 3,5-di-tert-butylquinone (3,5-DTBQ) at 400 nm (e = 1900 M À1 cm À1 ) for the catecholase-like activity at 25°C. Less than 5% of the conversion of the substrate to the product was monitored and the data were treated using the initial rate method as previously described [9].…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the pH range studied (4.75-8.5), the extinction coefficient of this product at 400 nm varies from 7180 at pH 4.5, 10 080 at 5.0; 11 400 at pH 5.5 to 12 000 at 6.0 and 12 100 at pH 6.5-8.5. 30 All assays were measured in 50 : 50 acetonitrile-buffer with the substrate and complex initially dissolved in acetonitrile. The aqueous multicomponent buffer was comprised of 50 mM 2-(N-morpholino)-ethanesulfonic acid (MES), 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), 2-(N-cyclohexylamino)ethane sulfonic acid (CHES) and N-cyclohexyl-3-aminopropanesulfonic acid (CAPS) with controlled ionic strength (LiClO 4 ) 250 mM.…”
Section: Kinetic Studiesmentioning
confidence: 99%